Pathophysiology of acute fibrinous and organizing pneumonia – Clinical and morphological spectra. Issue 3 (September 2019) - Santos, Cláudia; Oliveira, Rui Caetano; Serra, Paula; Baptista, João Pedro; Sousa, Eduardo; Casanova, Paula; Pimentel, Jorge; Carvalho, Lina
Abstract: Acute Fibrinous and Organizing Pneumonitis (AFOP) is a disease with histopathological pattern characterized by the presence of intra-alveolar fibrin in the form of fibrin "balls" and organizing pneumonia represented by inflammatory myofibroblastic polyps. Symptoms of this rare interstitial pulmonary disease can be either acute or sub-acute and it can rapidly progress to death. Diagnosis should be considered in the Intensive Care Unit (ICU) if patients' symptomatology and radiology correlates with non-responding or progressive pneumonia and when morphology, on biopsies, encompasses criteria of diffuse alveolar damage (DAD) and organizing pneumonia (OP) balancing in between. Three clinical cases of patients presenting severe lung disease requiring mechanical ventilation and prolonged intensive care fitted on the variable spectra of AFOP histopathology and had poor outcome: a 23 year-old women had AFOP in the context of antiphospholipid syndrome pulmonary compromise; a 35 year-old man developed a letal intensive care pneumonia with AFOP pattern registered in post-mortem biopsy; and a 79 year-old man died 21 days after intensive care unit treatment of a sub-pleural organizing pneumonia with intra-alveolar fibrin, seen in post-mortem biopsy. The predominance of acute fibrin alveolar deposition pattern is helpful in raising AFOP differential diagnosis while organizing pneumonia pattern establishes a wider range of diagnosis that can go till solitary pulmonary nodule, remaining indefinite to suggest diagnosis. The performance time of biopsy in a larger number of clinical cases may be helpful in establishing the evolutionary morphological pattern, taking in mind the poor outcome of the disease, deserving rapid diagnosis to define treatment.